Fabrication of Silicon Nanowire Field-Effect Transistor Biosensor by CMOS Compatible Top-Down Approach with Descum Process - Sohn, Young-Soo; Kang, Gil Bum; Kim, Yong Tae (AMER SCIENTIFIC PUBLISHERS, 2009)
A silicon nanowire field-effect transistor biosensor has been fabricated using the conventional "top-down" CMOS compatible technology with descum process for high-sensitive, real-time and label-free detection of a biomarker. Patterns generated from the conventional I-line stepper could be converted into silicon nanowire patterns, even sub-100 nm pattern by the descum process. The silicon nanowire biosensor was integrated with a microfluidic channel for the delivery of bio/chemicals to modify the surface of the silicon nanowire and to detect the biomarker. For the detection of the biomarker the surface of the silicon nanowire has been modified to immobilize specific receptor of the biomarker. Specific binding of the biomarker to the silicon nanowire surface would result in conductance change of the silicon nanowire The results have demonstrated the feasibility and potentiality of the silicon nanowire field-effect transistor biosensor. The descum process described in this work can be beneficial for easier integration with circuits and biosensor array, higher reproducibility, CMOS compatibility and low-cost mass production.
Keywords: ARRAYS; DNA